Circuit quantum acoustodynamics with surface acoustic waves - Manenti, R (2017)
A highly successful architecture for the exchange of single quanta between coupled quantum systems is circuit quantum electrodynamics (QED), in which the electrical interaction between a qubit and a high-quality microwave resonator offers the possibility to reliably control, store, and read out quantum bits of information on a chip. This architecture has also been implemented with mechanical resonators, showing that a vibrational mode can in principle be manipulated via a coupled qubit. The work presented in this thesis consists of realising an acoustic version of circuit QED that we call circuit quantum acoustodynamics (QAD), in which a superconducting qubit is piezoelectrically coupled to an acoustic cavity based on surface acoustic waves (SAWs). Designing and building this novel platform involved the following main accomplishments: a systematic characterisation of SAW resonators at low temperatures; successfully developing a recipe for the fabrication of Josephson junction on quartz and diamond; measuring the coherence time of superconducting 3D transmon qubits on these substrates and demonstrating the dispersive coupling between a SAW cavity and a qubit on a planar geometry. This thesis presents evidence of the coherent interaction between a SAW cavity and a superconducting qubit in several ways. First of all, a frequency shift of the mechanical mode as a function of qubit frequency is observed. We also measure the acoustic Stark shift of the qubit due to the population of the SAW cavity. The extracted coupling is in agreement with theoretical expectations. A time delayed acoustic Stark shift serves to further demonstrate that the Stark shifts that we observe are indeed due to the acoustic field of the SAW mode. The dispersive coupling between these two quantum systems offers the possibility to perform qubit spectroscopy using the SAW resonator as readout component, indicating that these acoustic resonators can, in principle, be adopted as an alternative qubit readout scheme in quantum information processors. We finally present preliminary measurements of the direct coupling between a SAW resonator and a transmon on diamond, suggesting that strong coupling can in principle be obtained.